PERCEIVED ORGANIZATIONAL SUPPORT AS MEDIATOR IN THE RELATIONSHIP BETWEEN EFFECTIVE HUMAN RESOURCES PRACTICE AND EMPLOYEE ENGAGEMENT IN INDONESIA - Djatmiko, Tri; Prasetio, Arif Partono; Azis, Elvira (Jurnal Aplikasi Manajemen, 2020)
The purpose of the study is to examine the impact of the effects of human resources practice (HRP) on employee engagement in Indonesia through the mediation of and perceived organizational support (POS). Recently, employee engagement has been a decline, and the organization has to take action to seek out what are the main factors that can help to stop the negative trend. Data collected using a questionnaire distributed to an individual who worked in private & public organizations in Bandung. It took 3 months to collect 350 responses. And from 250 valid participants, the study found that HRP and POS were a significant predictor of employee engagement. Employee whose perceived effective human resources practice and receive support from the organization, have stronger engagement. This study also found that POS mediate the relationship, which means that HR managers should be conducted in a way that provides convenience so that employees can perform better in their job. The limitation of the study is based on cross-sectional data and using self-reports for independent and dependent variables. The practical implication of the study is that since HRP and POS were found to influence engagement, this provides a model for management regarding important factors that can be enhanced to increase employee engagement. This study also provides a wider discussion regarding the impact of HRP and POS on engagement which still limited in a local domain. Future studies are suggested to cover more detailed participants from large organizations or certain industries to gather homogenous information regarding HRP, POS, and engagement. Besides, scholars could also implement deeper analysis using other statistical methods like Structural Equation Model. Lastly, future research can also examine other work behavior such as job satisfaction, organizational commitment, and leadership style which believed to have a great impact on engagement.